Controversies Regarding the Determination Standards of Online Child Pornography Offenses under the UN Convention against Cybercrime and China’s Countermeasures - Xiong, Yanni (International Journal of Social Sciences and Public Administration, 2025)
The criminalization of online child sexual exploitation material (CSEM) represents a global governance challenge. Within the framework of the United Nations Convention on Cybercrime, significant controversies persist regarding multiple standards for its legal definition. Concerning behavioral elements, disputes arise over the criminalization of mere possession or access and the criteria for establishing a profit-making purpose. Regarding the scope of the prohibited object, controversies exist on distinguishing between depictions of real children and virtual/simulated material, alongside regulatory difficulties concerning textual and audio representations. Pertaining to protected legal interests, conflicts emerge between the identification standards for "persons appearing to be children" and the safeguarding of creative freedom. The determination of such offenses should adhere to three core principles: the primacy of the child’s best interests, substantive assessment of the conduct, and consideration of dissemination impact. China should construct a multi-tiered governance framework. Legislatively, this entails introducing possession offenses and establishing quantitative thresholds. Judicially, it requires developing comprehensive evaluation rules for "persons appearing to be children" and defining standards for artistic creation exemptions. At the international level, efforts must strengthen collaborative governance mechanisms within the Convention framework to balance cultural differences with the imperative of child protection.